The Influence of Motivation, Communication and Work Culture on Employee Performance at PT. Plantation Nusantara IV Medan - Farhan Azmi; Muhammad Toyib Daulay; Kiki Farida Ferine (International Journal of Society and Law, 2024)
This study aims to find out whether motivation, communication and work culture affect employee performance. The data analysis technique used in this study is an associative research method with the help of the SPSS version 20 application program. This study uses multiple linear regression analysis. The sample used in this study amounted to 34 respondents. The data used in this study is using primary data obtained from the results of the questionnaire distributed to the respondents. The results of the study show that motivation has a positive and partially significant effect on employee performance at PT. Nusantara IV Plantation Medan. Communication has no effect and is not partially significant on employee performance at PT. Nusantara IV Plantation Medan. Work culture has a positive and partially significant effect on employee performance at PT. Nusantara IV Plantation Medan. Motivation, communication and work culture simultaneously have a positive and significant effect on employee performance at PT. Nusantara IV Plantation Medan.